2019
DOI: 10.37358/rc.19.3.7001
|View full text |Cite
|
Sign up to set email alerts
|

Tarnita Polluted Area: Accumulation of Heavy Metals and Nutrients from the Soil by Woody Species

Abstract: Heavy metals are destructive environmental stressors that greatly reduce plant growth and productivity. Here, the content of some heavy metals (Fe, Cu, Zn and Mn) and mineral nutrients (Ca, Mg and K) in silver fir (Abies alba Mill.) and European beech (Fagus sylvatica L.) wood from two sites in the Tarni�a mining area (North-Est Romania) was analyzed. The first site (no. 1) is located near a big tailings dump, whereas the other one (no. 2) is situated 6 km South, in a less polluted area. The purpose of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In order to highlight the level of pollution intensity on the silver fir and Norway spruce stands in the Tarnit , a area, the 30 plots were located spatially at different distances from the main source of pollution. Taking into account previous research [19,20], in which several stands located at different distances from the source of pollution were analyzed and it was concluded that the 2 km length was the approximate distance to and from which the stands were affected by pollution to varying degrees of intensity, we tested this hypothesis and we considered in this study that intensively polluted stands are located at a maximum distance of 2 km from the main source of pollution, moderately polluted stands are located between 2 and 6 km and largely unpolluted stands are located at a distance greater than 6 km. Thus, based on the results obtained in these studies, in order to test our hypothesis, we considered these distances as limits between different pollution intensities.…”
Section: Methodsmentioning
confidence: 92%
“…In order to highlight the level of pollution intensity on the silver fir and Norway spruce stands in the Tarnit , a area, the 30 plots were located spatially at different distances from the main source of pollution. Taking into account previous research [19,20], in which several stands located at different distances from the source of pollution were analyzed and it was concluded that the 2 km length was the approximate distance to and from which the stands were affected by pollution to varying degrees of intensity, we tested this hypothesis and we considered in this study that intensively polluted stands are located at a maximum distance of 2 km from the main source of pollution, moderately polluted stands are located between 2 and 6 km and largely unpolluted stands are located at a distance greater than 6 km. Thus, based on the results obtained in these studies, in order to test our hypothesis, we considered these distances as limits between different pollution intensities.…”
Section: Methodsmentioning
confidence: 92%
“…Normal amounts of copper and zinc have a positive effect on the biological resistance of plants to low and high temperatures and soil salinity. Copper can, to some extent, affect the uptake of nitrogen by plants, and zinc enhances the growth and development of the root system and is important for plant fruiting processes (Skarlyna-Ufimtseva 1980; Barbieri 2016; Iacoban et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heavy metals with concentration levels in the soil higher than 0,1 % become toxic for plants, altering the structure of the plant community in a polluted habitat [3,8,9,22,[27][28][29][30][31][32][33][34][35][36][37].…”
mentioning
confidence: 99%